Research on technology of data encryption and search based on access broker - Guofeng WANG; Chuanyi LIU; Peiyi HAN; Hezhong PAN; Binxing FANG (Tongxin xuebao)
Broker executed searchable encryption (BESE) scheme was proposed for the confidentiality issues of cloud application data.The scheme did not need to modify the cloud application or user habits,thus had strong applicability.Firstly,systematic and quantitative analysis on BESE scheme was conducted in terms of query expressiveness,performance and security.Then,the main challenges of BESE scheme including securely sharing index and encrypted data between brokers were pointed out,and corresponding schemes were proposed to address the above challenges.The experimental results show that the BESE scheme can effectively protect the user data in the cloud,achieve a variety of search functions,and has high efficiency and security.